Adaptatividade e resiliência no sistema socioecológico da comunidade caiçara da Ilha Diana, município de Santos-SP - Stori, Fernanda Terra (2010)
In this study we present the case of Ilha Diana caiçara community (Santos, Brazil), which is passing through significant transformations as the artisanal fishing activity declines and the industrial-port complex expands through this territory. We discuss which elements configure adaptability and resilience to the social-ecological system that evolves the Ilha Diana caiçara community in order to build resilience. The aims were the qualitative identification of caiçara cultural aspects, of social mechanisms and management traditional practices of the fishing resources and their transformations (1), as well as the analysis of the social-technological net logique d action composed by the emergent controversy of the environmental licensing of a modern port terminal (2). Proceeding the first analysis, we adopted an ethnoecological approach interviewing 20 Ilha Diana inhabitants (9% of the resident population), with ages varying from 18 to 90 years, respecting the equity between genders. Proceeding the second analysis, ten social stakeholders evolved at the controversy of port expansion were interviewed. Particular aspects of caiçara culture were identified at Ilha Diana territory, as its social organization linked to fishery and the self-recognition of this culture. We identified seven fishing management practices based on the local ecological knowledge, four social mechanisms connected to those practices, three innovation technological practices and the extinction of a traditional practice of selective fishery. The intergenerational loss of ecological knowledge and its linked social mechanisms can decrease resilience in this social-ecological system. However, the social mechanisms here identified may be a counterbalance to the negative aspects of crisis, promoting the re-organization of the system. We also noticed that the commercial and industrial logique d action , dominant worldviews within the ambit of the studied territory exert a negative influence for the maintenance of fishing practices and caiçara social mechanisms of Ilha Diana. The civic, domestic and opinion logics are only the counterpoint to the dominant views, as social-environmental conditions to licensing process of significant environmental impact undertakings. Thus we could not observe a real translation process of the analyzed licensing merely a process of negotiating conditions resulting in suspicions and conflicts which demonstrated that the concerning net is not wide, strengthened, attentive and clear. Then, we conclude that the promotion of resilience within the ambit of the studied social-ecological system will depend on the adaptive ability of the community, starting with sustainable socioeconomic practices, as, for instance, those based on their cultural upgrading. We think that it will also depend on debates with wide popular participation about the Santos estuarine portuary development projects, on a clear way, in terms of strengthening the concerning nets and elevate the vigilance upon them.